Nature’s sustainable aqua gift: Pearl in Unani medicine - Rabbani, Mumtaz; Kartika, Betania; Hashim, Khairusy Syakirin Has-Yun (HH Publisher, 2020)
The Unani medical system is a holistic approach of science and the human body. It is a natural and simple method of extracting from nature and based on the way body responses. Contrary to the prevalent credence, good health is always associated with nutritious food and active lifestyle, but historical facts have laid a sturdy substructure that a natural gem-like Pearl has higher impact rate on the human body. Reports indicate that India is one of the top countries welcoming more medical tourists and the industry is expected to grow to $8 billion this year. This paper explains the importance of sustaining the Unani system and drugs made from a component (Pearl-Marwareed) obtained from a marine animal, providing insight on good aquaculture practice in India. Hence, exploring the Islamic perspective of Unani medicine, the safety contour of the drugs and the usage of pearl in its composition. The data were collected from personal interviews with Hakeem (physicianswith wisdom) across India and extensive literature. This paper recommends to promote Unani medical tourism in India. Thus, generating positive statistics and providing significant sustainable strategies for further improvement in the Aquaculture industry. Policymakers and researchers need to focus more on implementation of best techniques and technology to develop Indian traditional products and their usage in traditional medicinal system ‘Unani’.